Correlation of Power Consumption of Double Impeller Based on Impeller Spacing in Laminar Region - Haruki Furukawa; Toshiki Kamiya; Yoshihito Kato (International Journal of Chemical Engineering)
Power consumption is an important parameter for the design of mixing equipment. The aim of this study is to develop a new correlation of the power consumption of a double impeller. The effect of impeller spacing on the double-impeller flow pattern and power consumption was investigated in the laminar region. As a result, the effect of impeller spacing on the flow pattern was described based on the ratio of impeller spacing to the impeller blade height. Moreover, the power consumption of a double impeller could be correlated with the same ratio.